Ikhtiar Peningkatan Keterwakilan melalui Pembentukan Dapil Luar Negeri: Evaluasi terhadap Pemilu - Rahadian Diffaul Barraq Suwartono (Fakultas Hukum Universitas Islam Indonesia, 2023)
Approaching the 2023 Indonesian General Elections, the issue of establishing overseas electoral ballots is revolving. This issue has actually been proclaimed for a long time, at least since the filing for a judicial review of Law No. 8 of 2012 which was decided by the Constitutional Court in 2013. However, until now, this issue has not been fulfilled and a comprehensive discussion has not been held by the relevant parties. This article tries to examine the establishment of overseas electoral ballots as an effort to achieve representation for the Indonesian diaspora. This article is normative legal research enacted into two problem formulations, namely: How is the representation of Indonesian citizens abroad in the DPR so far? How can the formation of Overseas Ballots maximize the representation of Indonesian Citizens abroad in the DPR? The legal materials used are Indonesian Laws, Constitutional Court Decision Number 2/PUU-XI/2013, and several secondary legal sources in the form of books, previous research articles, and trusted web sources. This article concludes: the representation of the Indonesian diaspora has not been represented. The formation of Overseas Electoral Ballots must also be able to encourage the emergence of legislative candidates who are familiar to the people and understand the issues experienced by the Indonesian diaspora.